Regeneration of subalpine conifer species is inhibited by bark-stripping deer in a Betula forest - Takuo Nagaike; Hayato Iijima (Arctic, Antarctic, and Alpine Research)
Climate change is expected to alter biotic interactions governing tree species ranges. Identifying the limiting demographic processes controlling tree distribution is key to projecting future range shifts. A preference by herbivores for stripping the bark of tree species undergoing range shifts could inhibit tree range shifts. We focused on the effects of bark stripping by recently arrived sika deer (Cervus nippon) on the survival of subalpine conifers (Abies spp.) in a Betula ermanii forest in central Japan. Abies spp. which currently occur at lower elevations than B. ermanii but are predicted to expand to higher elevations with climate change, were less abundant than B. ermanii on Mt. Kita, central Japan, and were preferred by sika deer for bark stripping. The ratio of the number of stripped Abies stems to the total number of stripped stems was unrelated to elevation. Because of the lower dominance of Abies spp. at higher elevations, bark-stripping pressure on them would be stronger there. Both bark stripping by deer and competition (intra- and interspecific) contribute to the death of Abies spp. Our results suggest that bark-stripping herbivores can be an important contributing factor hampering upward range shifts of Abies spp.